SUATU KAJIAN DESKRIPTIF BIMBINGAN KONSELING TERHADAP PERILAKU KECANDUAN MENONTON VIDEO PORNO DAN SEKS BEBAS PADA REMAJA MASA KINI (SEX BEFOREMARRIAGE) - Frieska Putrima Tadung; Diana Sari Yosepin Lakumani; Geysya Flinjili Rotikan (Institut Agama Kristen Negeri Manado, 2023)
One of the reasons for doing this research is that adolescence is a period of transition from childhood to adulthood. During growth and development, adolescents experience changes that require them to adapt. However, it cannot be denied that many young people at this developmental stage are unable to adapt, causing problems that affect their development in life, such as the current prevalence of addictive behaviors such as pornography viewing and free sex. Maladjustment is caused by several factors, including youth quality, family quality, lack of quality information, and environmental quality. Researchers believe that suggestions are needed to help young people solve this problem. This study uses a qualitative descriptive research methodology. The research target is high school teenager.